The Life of Benjamin Franklin. Vol. 2: Printer and Publisher, 1730-1747. - Burstein, Andrew (American Historical Review, 2007)
Reviewed: The Life of Benjamin Franklin. Vol. 2: Printer and Publisher, 1730-1747. Lemay, J. A. Leo.